2012
DOI: 10.2174/1874357901206010216
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Global mRNA and miRNA Profiling of HPV-Positive Cell Lines and Clinical Specimens

Abstract: For more than a decade, global gene expression profiling has been extensively used to elucidate the biology of human papillomaviruses (HPV) and their role in cervical- and head-and-neck cancers. Since 2008, the expression profiling of miRNAs has been reported in multiple HPV studies. Two major strategies have been employed in the gene and miRNA profiling studies: In the first approach, HPV positive tumors were compared to normal tissues or to HPV negative tumors. The second strategy relied on analysis of cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 88 publications
(156 reference statements)
0
18
0
Order By: Relevance
“…HPV 68 has been classified as probable high-risk (also known as IARC class 2A) and another seven types have been classified as possible high-risk (HPV 26,53,66,67,70,73 and 82;also known as IARC class 2B) 5 .…”
Section: Cervical Cancer and Hpvmentioning
confidence: 99%
“…HPV 68 has been classified as probable high-risk (also known as IARC class 2A) and another seven types have been classified as possible high-risk (HPV 26,53,66,67,70,73 and 82;also known as IARC class 2B) 5 .…”
Section: Cervical Cancer and Hpvmentioning
confidence: 99%
“…Previously, our group and others found that HPV infection regulates the expression of keratinocyte miRNAs (18)(19)(20) and that aberrant miRNA expression in CC and its derived cell lines is important for cancer cell proliferation (21)(22)(23)(24). However, the different approaches used led to varied observations (25,26). To date, there is no systematic study to identify host miRNAs as specific biomarkers for diagnosis of HPV infection or progression.…”
Section: Significancementioning
confidence: 99%
“…An earlier study on the global mRNA and miRNA profiling in HPV-positive cell lines observed that different HPV types in dissimilar biological conditions may also affect the same pathway, but genes involved may be different. 24 Similarly, another study on the role of miRNA in HPV-associated cancers indicated that a set of miRNAs was shared exclusively by HPV-positive head and neck squamous cell carcinoma and cervical squamous cell carcinoma compared with the number of miRNAs shared exclusively by HPV-negative head and neck squamous cell carcinoma and cervical squamous cell carcinoma. 25 Thus, all these data show that carcinogenic mechanism may be similar in HR-HPV infection irrespective of different HPV types.…”
Section: Discussionmentioning
confidence: 99%